2014
DOI: 10.1038/ejcn.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption is inversely associated with the metabolic syndrome

Abstract: We found that increased fish intake was independently related to the lower odds of metabolic syndrome and its features. Further prospective investigations are warranted to confirm this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 53 publications
10
70
2
1
Order By: Relevance
“…It is also a fact that fish consumption is more common in some parts of Iran which are closer to the sea (Caspian Sea and Persian Gulf); but in other regions, fish is not a common food in daily diet of people and it is rarely consumed. Although the mean daily consumption of fish was higher in our study than previous studies (20), a study in Iran revealed that the gap between the current fish consumption and the amounts necessary for maintaining healthy diet is still far from satisfactory (21).…”
Section: Discussioncontrasting
confidence: 85%
“…It is also a fact that fish consumption is more common in some parts of Iran which are closer to the sea (Caspian Sea and Persian Gulf); but in other regions, fish is not a common food in daily diet of people and it is rarely consumed. Although the mean daily consumption of fish was higher in our study than previous studies (20), a study in Iran revealed that the gap between the current fish consumption and the amounts necessary for maintaining healthy diet is still far from satisfactory (21).…”
Section: Discussioncontrasting
confidence: 85%
“…This might suggest a dose-response relationship between lean fish consumption and WC. However, results are conflicting, and not all studies have observed significant associations between fish consumption and a decrease in WC [17,22]. However, in these studies, fatty and lean fish were not assessed separately.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, higher fish consumption has been associated with an increased HDL-C in both men [17] and women [22]. However, when fatty fish consumption and lean fish consumption were examined separately in intervention studies, a significant increase in HDL-C was reported for fatty fish [51,52], but not for lean fish [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations